PENGAPLIKASIAN ILMU HADITS DALAM MENANGKAL HOAX DI MEDIA SOSIAL - Nurlaili Fauziah; Nirwan Syafrin; Kholil Nawawi (Universitas Pahlawan Tuanku Tambusai, 2022)
The science of hadith is a science that talks about the status of hadith, as well as the nature of the narrators who narrate hadith. Narrators are people who receive, carry, and convey news from the Prophet. Hadith is a khobar or news. When a hadith is narrated, the source must be clear, who is the narrator or who brought it, if there is a defect / 'illat of one of the narrators then the hadith will not be accepted. Likewise with news or information that is conveyed and received among the public, especially people who use social media. The purpose of this study is to determine the phenomenon of hoaxes that are spread on social media and the application of hadith science in counteracting hoaxes. The writing uses qualitative research methods with the type of library research research and the research approach uses content analysis . The results of the study show that the biggest phenomenon of spreading hoaxes on social media is Facebook, and the application of hadith knowledge in countering hoaxes on social media can be done by three methods (sanad criticism, source authority, and validity). The limitation or weakness of this research is the research method that uses library research , sometimes the data collected is still less relevant. Researchers have tried as much as possible to minimize the existing shortcomings. And it is hoped that this research can be used as a reference for similar studies. The benefit of this research is to provide input, insight, and knowledge related to the application of hadith science in countering hoaxes on social media and is expected to be a reference in conducting similar research. Keywords: Application, Hadith Science, Counteracting, Hoax, Social Media.